Improved cognition and preserved hippocampal fractional anisotropy in subjects undergoing carotid endarterectomy “CEA preserves cognition & hippocampal structure” - Bernstein, Adam; Arias, Juan C.; Howell, Caronae; French, Scott; Guzman, Gloria; Bruck, Denise; Berman, Scott; Leon, Luis; Pacanowski, John; Tan, Tze-Woei; Altbach, Maria; Trouard, Theodore; et al. (Journal of stroke and cerebrovascular diseases, 2024)
A growing body of data indicates that extracranial carotid artery disease (ECAD) can contribute to cognitive impairment. However, there have been mixed reports regarding the benefit of carotid endarterectomy (CEA) as it relates to preserving cognitive function. In this work, diffusion magnetic resonance imaging (dMRI) and neurocognitive testing are used to provide insight into structural and functional brain changes that occur in subjects with significant carotid artery stenosis, as well as changes that occur in response to CEA. The study design was a prospective, non-randomized, controlled study that enrolled patients with asymptomatic carotid stenosis. Thirteen subjects had severe ECAD (≥70% stenosis in at least one carotid artery) and were scheduled to undergo surgery. Thirteen had asymptomatic ECAD with <70% stenosis, therefore not requiring surgery. All subjects underwent neurocognitive testing using the Montreal Cognitive Assessment test (MoCA) and high angular resolution, multi-shell diffusion magnetic resonance imaging (dMRI) of the brain at baseline and at four-six months follow-up. Changes in MoCA scores as well as in Fractional anisotropy (FA) along the hippocampus were compared at baseline and follow-up. At baseline, FA was significantly lower along the ipsilateral hippocampus in subjects with severe ECAD compared to subjects without severe ECAD. MoCA scores were lower in these individuals, but this did not reach statistical significance. At follow-up, MoCA scores increased significantly in subjects who underwent CEA and remained statistically equal in control subjects that did not have CEA. FA remained unchanged in the CEA group and decreased in the control group. This study suggests that CEA improves cognition and preserves hippocampal white matter structure compared to control subjects not undergoing CEA.